2017
DOI: 10.1371/journal.pone.0179123
|View full text |Cite
|
Sign up to set email alerts
|

The proximal experience of gratitude

Abstract: Although a great deal of research has tested the longitudinal effects of regularly practicing gratitude, much less attention has been paid to the emotional landscape directly following engagement in gratitude exercises. In three studies, we explored the array of discrete emotions people experience after being prompted to express or recall gratitude. In Studies 1 and 2, two different gratitude exercises produced not only greater feelings of gratitude relative to two positive emotion control conditions (i.e., re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 90 publications
7
60
0
2
Order By: Relevance
“…Our findings suggest that awe experiences (including experimental inductions of awe) are not only awe-inspiring, but that they may also give rise to a range of positive states, including several discrete self-transcendent emotions and positive emotions in general, as well as self-relevant thoughts and connectedness to others. Much like Layous and colleagues [39] found that gratitude is not the only or strongest outcome of a gratitude induction, we found that awe is not the only or strongest outcome of an awe induction. Indeed, in both of our studies, we found that compassion was the strongest emotion elicited in response to our manipulation, and compassion was elicited more strongly than awe in our second study.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings suggest that awe experiences (including experimental inductions of awe) are not only awe-inspiring, but that they may also give rise to a range of positive states, including several discrete self-transcendent emotions and positive emotions in general, as well as self-relevant thoughts and connectedness to others. Much like Layous and colleagues [39] found that gratitude is not the only or strongest outcome of a gratitude induction, we found that awe is not the only or strongest outcome of an awe induction. Indeed, in both of our studies, we found that compassion was the strongest emotion elicited in response to our manipulation, and compassion was elicited more strongly than awe in our second study.…”
Section: Discussionsupporting
confidence: 82%
“…According to Kashdan et al (2009), gratitude is a simple construct for people to grasp; thus, it can be measured successfully with one or two items. This assumption has been also confirmed by the results of studies on gratitude in which very short measures were used instead of multiple-item scales (Graham 1988;Jans-Beken et al 2018;Layous et al 2017;Visserman et al 2018). Taking into consideration these premises and the fact that in this study the respondents were asked about levels of gratitude toward specific, well-defined persons from their lives, measurement using single items was found to be adequate and sufficient.…”
Section: Gratitude Toward Different Interpersonal Targetssupporting
confidence: 70%
“…Positive activity interventions experimentally test the practice of simple, self-administered cognitive and behavioral strategies that can increase subjective well-being by promoting positive feelings, positive thoughts, and positive behaviors . For example, activities such as counting one's blessings (Chancellor, Layous, & Lyubomirsky, 2015;Emmons & McCullough, 2003;Froh, Sefick, & Emmons, 2008;Seligman, Steen, Park, & Peterson, 2005), writing letters of gratitude Layous, Lee, Choi, & Lyubomirsky, 2013;Layous et al, 2017;Lyubomirsky, Dickerhoof, Boehm, & Sheldon, 2011;Seligman et al, 2005), and performing acts of kindness (Chancellor, Margolis, Jacobs Bao, & Lyubomirsky, 2018;Dunn, Aknin, & Norton, 2008;Layous et al, 2013;Nelson et al, 2015;Nelson, Layous, Cole, & Lyubomirsky, 2016;Sheldon, Boehm, & Lyubomirsky, 2012) have been shown to reliably boost well-being. If administered optimally, positive activity interventions can also build positive psychological resources such as social connections and meaning in life, as well as ameliorate existing maladaptive symptoms such as anxiety and rumination (Layous, Chancellor, & Lyubomirsky, 2014;Seligman, Rashid, & Parks, 2006;Seligman et al, 2005;Shin & Lyubomirsky, 2016;Sin & Lyubomirsky, 2009;Taylor, Lyubomirsky, & Stein, 2017).…”
mentioning
confidence: 99%